2023
DOI: 10.52567/pjsr.v5i02.1178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Capital Structure on the Firm Performance: Moderating Role of Firm Size

Abstract: The primary aim of the research was to explore the influence of capital structure based on the business performance in context to the moderating role of firm size. In consideration of the main aim of the study, the objectives of the research were to comprehend the notion of the impact of capital structure on the firm performance with regards to the moderating role of firm size, to examine the factors affecting the capital structure on the firm performance in context to the moderating role of firm size, to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A firm's capital structure, which includes a mix of debt and equity financing, significantly affects its financial performance and risk exposure. Traditional finance theories, such as the Modigliani and Miller Theory, emphasise the importance of striking a balance between the tax benefits of debt and the drawbacks associated with financial distress and agency conflicts arising from high leverage [21], [22]. Research has shown that the composition of capital structure, including short-term debt, long-term debt, and equity, impacts firm performance in various sectors [23].…”
Section: Capital Structure and Financial Performancementioning
confidence: 99%
“…A firm's capital structure, which includes a mix of debt and equity financing, significantly affects its financial performance and risk exposure. Traditional finance theories, such as the Modigliani and Miller Theory, emphasise the importance of striking a balance between the tax benefits of debt and the drawbacks associated with financial distress and agency conflicts arising from high leverage [21], [22]. Research has shown that the composition of capital structure, including short-term debt, long-term debt, and equity, impacts firm performance in various sectors [23].…”
Section: Capital Structure and Financial Performancementioning
confidence: 99%